Teachers’ Experiences on Virtual Class During COVID-19 Crisis: Challenges and its Coping Measures - Gurung, Gem Prasad; Ghimire, Rajan (ILAM इलम, 2026)
This study explores the experiences of science teachers who faced the COVID-19 crisis which was accidentally spread in Nepal as well as in the world. In response to the coronavirus crisis followed a series of lockdowns to save human lives and the Government decided to close all the educational institutions. After some months, the Government or University introduced a notice to resume (conduct) the class school and university classes. However the study found without preparation of online learning and quality technology, many teachers and students experienced a series of challenges to conduct the online classes. The research objectives were adopted to find out the challenges that teachers faced in online classes during the COVID-19 crisis, to explore the emergency response in education during the pandemic, and to find out coping measures for future emergencies. As the nature of objectives, qualitative method was followed and interview guidelines were used for in-depth interviews with teachers for necessary data collection. The literature review consists of the preparation of digital literacy and adequate quality of digital connectivity. The study also attempts that the ongoing COVID-19 pandemic has not only created a problem but also revolutionized the educational system and forced fundamental changes in the teaching and learning process. The contributions of this study make awareness to stay in a ready position i.e., management of connectivity, tools, and platforms for online education in any crisis.